Shear wave velocity versus quality factor: results from seismic noise recordings. Issue 2 (26th April 2017) - , Tobias; Boxberger,; Pilz, Marco; Parolai, Stefano
Abstract: The assessment of the shear wave velocity ( vs ) and shear wave quality factor ( Qs ) for the shallow structure below a site is necessary to characterize its site response. In the past, methods based on the analysis of seismic noise have been shown to be very efficient for providing a sufficiently accurate estimation of the vs versus depth at reasonable costs for engineering seismology purposes. In addition, a slight modification of the same method has proved to be able to provide realistic Qs versus depth estimates. In this study, data sets of seismic noise recorded by microarrays of seismic stations in different geological environments of Europe and Central Asia are used to calculate both vs and Qs versus depth profiles. Analogous to the generally adopted approach in seismic hazard assessment for mapping the average shear wave velocity in the uppermost 30 m ( vs 30 ) as a proxy of the site response, this approach was also applied to the quality factor within the uppermost 30 m ( Qs 30 ). A slightly inverse correlation between both parameters is found based on a methodological consistent determination for different sites. Consequently, a combined assessment of vs and Qs by seismic noise analysis has the potential to provide a more comprehensive description of the geological structure below a site.